# Question #89f06

##### 2 Answers

#### Answer

#### Answer:

#### Explanation

#### Explanation:

#### Answer:

Please see below for (2).

#### Explanation:

Using

# = lim_(nrarroo)sum_(i=1)^n i^27/n^27 * 1/n#

# = lim_(nrarroo)sum_(i=1)^n (i/n)^27 * 1/n#

#### Answer

#### Answer:

#### Explanation

#### Explanation:

Describe your changes (optional) 200

#### Answer:

Please see below for (1).

#### Explanation:

Using

So

has

So

Observe that when

In this case we get

We have

# lim_(nrarroo)sum_(i=1)^n 2e^sqrt(0+i/n) 1/n#

So

and we get

Describe your changes (optional) 200